Market Performance, Roe, Cash Flow Dan Keputusan Investasi Dengan Cash Holdings Sebagai Moderasi Pada Perusahaan Manufaktur Di Indonesia - I Made Sudana; Heti Rachmawati (Universitas Airlangga, 2017)
This study aims to determine the effect of market perfomance, ROE, cash flow and investment decisions with cash holdings as a moderating in manufacturing company in Indonesia which is listed on the Stock Exchange from 2012 to 2015. This study took 112 manufacturing companies in Indonesia. Research methods band is used in this study using purposive sampling method. Dependent variable in this research is investment decisions were measured by capital expenditure. Independent variables in this study is the market performance measured by Tobin's q, return on equity, cash flow, while moderating variable in this study is cash holdings. The method used in this research is multiple linear regression analysis. The results of this study significantly show that market performance, cash flow positive influence on investment decisions, while ROE negative effect on investment decisions. The influence of of cash flow to capital expenditure is moderated by cash holding that indicated by significant negative influence.